Emojis e Hashflags: uma análise sóciorretórica da linguagem multissemiótica do Twitter - Mattos, Elisa; Brasil, Vanessa; Garcia, Gustavo; Oliveira, Nivia Aniele (Revista Leitura, 2019)
<span style="font-size: 12pt; font-family: ’EB Garamond’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Este artigo apresenta uma análise de emojis mapeados em 15 tuítes, nos quais a confluência de modos semióticos é primordial para a construção de sentido, para a organização sóciorretórica do gênero discursivo microblog e para a escolha dos emojis. Considerando os pressupostos teóricos de Conole e Dyke (2004), Kress (2010), Kress e van Leeuwen (2006) e Danesi (2017), os tuítes foram analisados e os emojis foram categorizados segundo Danesi (2017). A análise revela que, nos tuítes examinados, os emojis são empregados em três funções: sintática, como pontuação; semântica, substituindo itens lexicais; e enfática, como marcadores discursivos. A análise também identificou a presença de hashflags, um novo tipo de hashtag da qual emojis customizados são acionados. Nas hashflags dos tuítes analisados, os emojis atuam como índice simbólico do conteúdo semântico-pragmático da hashtag, evidenciando a interdependência entre os modos semióticos constitutivos dos tuítes, bem como a dinamicidade das affordances do ambiente digital. <span style="font-size: 12pt; font-family: ’EB Garamond’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> <span style="font-size: 12pt; font-family: ’EB Garamond’; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> <span style="font-size: 12pt; font-family: ’EB Garamond’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Emojis and Hashflags: a socio-rhetorical analysis of the Twitter’s multi-semiotic language <span style="font-size: 12pt; font-family: ’EB Garamond’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">This paper presents an analysis of emojis mapped in 15 tweets, in which the confluence of semiotic modes is seen as the foundation for meaning construction, for the socio-rhetorical structure of the genre microblog and for the choice of emojis used in the tweets. Based on the theoretical assumptions of Conole and Dyke (2004), Kress (2010), Kress and van Leeuwen (2006) and Danesi (2017), the tweets were analyzed and the emoji were categorized according to Danesi (2017). The analysis reveals that, in the tweets examined, the emojis have been employed according to three functions: syntactic, as punctuation marks; semantic, replacing lexical items; and emphatic, as discourse markers. The analysis also identified hashflags, a new type of hashtag from which custom emojis are triggered. In the hashflags present in the analyzed tweets, the custom emojis act as a symbolic index of the semantic-pragmatic content of the hashtag, thus revealing the interplay between the semiotic modes in the tweets and the dynamic nature of the digital affordances. <span style="font-size: 12pt; font-family: ’EB Garamond’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;"> <span style="font-size: 12pt; font-family: ’EB Garamond’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">DOI: <span style="font-size: 12pt; font-family: ’EB Garamond’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">10.28998/2317-9945.2019n63p47-69<span style="font-size: 12pt; font-family: ’EB Garamond’; color: #000000; background-color: transparent; font-weight: 400; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">